Minocycline impairs TNF-α-induced cell fusion of M13SV1-Cre cells with MDA-MB-435-pFDR1 cells by suppressing NF-κB transcriptional activity and its induction of target-gene expression of fusion-relevant factors - Julian Weiler; Thomas Dittmar (Cell Communication and Signaling, 2019)
Abstract Background To date, several studies have confirmed that driving forces of the inflammatory tumour microenvironment trigger spontaneous cancer cell fusion. However, less is known about the underlying factors and mechanisms that facilitate inflammation-induced cell fusion of a cancer cell with a normal cell. Recently, we demonstrated that minocycline, a tetracycline antibiotic, successfully inhibited the TNF-α-induced fusion of MDA-MB-435 cancer cells with M13SV1 breast epithelial cells. Here, we investigated how minocycline interferes with the TNF-α induced signal transduction pathway. Methods A Cre-LoxP recombination system was used to quantify the fusion of MDA-MB-435-pFDR1 cancer cells and M13SV1-Cre breast epithelial cells. The impact of minocycline on the TNF-α signalling pathway was determined by western blotting. The transcriptional activity of NF-κB was characterised by immunocytochemistry, western blot and ChIP analyses. An NF-κB-luciferase reporter assay was indicative of NF-κB activity. Results Minocycline treatment successfully inhibited the TNFR1-TRAF2 interaction in both cell types, while minocycline abrogated the phosphorylation of IκBα and NF-κB-p65 to suppress nuclear NF-κB and its promotor activity only in M13SV1-Cre cells, which attenuated the expression of MMP9 and ICAM1. In MDA-MB-435-pFDR1 cells, minocycline increased the activity of NF-κB, leading to greater nuclear accumulation of NF-κB-p65, thus increasing promoter activity to stimulate the expression of ICAM1. Even though TNF-α also activated all MAPKs (ERK1/2, p38 and JNK), minocycline differentially affected these kinases to either inhibit or stimulate their activation. Moreover, SRC activation was analysed as an upstream activator of MAPKs, but no activation by TNF-α was revealed. The addition of several specific inhibitors that block the activation of SRC, MAPKs, AP-1 and NF-κB confirmed that only NF-κB inhibition was successful in inhibiting the TNF-α-induced cell fusion process. Conclusion Minocycline is a potent inhibitor in the TNF-α-induced cell fusion process by targeting the NF-κB pathway. Thus, minocycline prevented NF-κB activation and nuclear translocation to abolish the target-gene expression of MMP9 and ICAM1 in M13SV1-Cre cells, resulting in reduced cell fusion frequency.